REDressing Invisibility and Marking Violence Against Indigenous Women in the Americas Through Art, Activism and Advocacy - Johnson, Shelly; Santos, Alessandra (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
The incidence of crimes against Indigenous women in the Americas has a long history in the making, but in remembering this history now, in redressing the invisible violence, in rendering the invisible visible, is how we as community can put a stop to the atrocities. Two Indigenous women academics from north and south America explore the intersections between art, activism and advocacy in this article on missing, raped and murdered Indigenous women in Mexico, Guatemala and Canada. It asks questions and provides examples about how artists, activists and advocates can redress the invisibility of the violence against Indigenous women, violations of their human rights and potentially repair loss.